2014
DOI: 10.1039/c3lc50977j
|View full text |Cite
|
Sign up to set email alerts
|

A continuous-flow high-throughput microfluidic device for airborne bacteria PCR detection

Abstract: Rapid analysis of airborne pathogens plays a critical role in early warning of spreading infectious diseases, which is essential for public health and disease prevention. Herein we report an integrated microfluidic device that can perform airborne pathogen capture, enrichment and continuous-flow high-throughput gene analysis. The device was validated by six frequently encountered bacteria and shows great potential in environmental analysis and for public health protection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 22 publications
0
30
1
2
Order By: Relevance
“…The state of each valve can be precisely controlled (Fig. 1C), and the entire operation was programmed with LabView in semi-automatic and fully automatic modes [21]. The system could be used by technicians with minimum training, because minimal human intervention is required for the operation.…”
Section: General Setupmentioning
confidence: 99%
See 1 more Smart Citation
“…The state of each valve can be precisely controlled (Fig. 1C), and the entire operation was programmed with LabView in semi-automatic and fully automatic modes [21]. The system could be used by technicians with minimum training, because minimal human intervention is required for the operation.…”
Section: General Setupmentioning
confidence: 99%
“…Various immunoassays [18] that have been miniaturized into microfluidic chips have the advantages of minimal reagent consumption, high-throughput operation, low cost, easy automation, and portability [19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Jiang et al created a nearly fully automated continuous flowthrough microfluidic apparatus that was capable of bioaerosol capture and detection of six separate aerosolized bacterial targets. 162 Including sampling, lysis, and on-chip nucleic acid amplification, the total assay time was 1 h 10 min, with a detection limit <10 3 CFUs per mL. Separate gel electrophoresis was required for detection, but existing methods can be implemented into this protocol for (relatively) rapid detection.…”
Section: Pcr and Nucleic Acid Detectionmentioning
confidence: 99%
“…In designing a system, concentration rate should be optimized by increasing the air flow rate and collection efficiency, or decreasing the volume of capture liquid preferably to microfluidic volumes, because this improves the aerosol detection sensitivity. Past studies reconciling microfluidics with aerosol collection (by deposition of aerosol in channels/half-channels) have reported concentration rates of 10 4 -10 6 min ¡1 , and have delineated the limitations with these approaches (Han and Mainelis 2008;Han et al 2010Han et al , 2011Jing et al 2013Jing et al , 2014Pardon et al 2015;Han et al 2015a,b;Foat et al 2016;Ma et al 2016). These studies have shown successes, but require further work in integration with assay platforms, clearly demonstrating end-to-end bioaerosol collection and identification, estimating limits of detection, and detailed field testing.…”
Section: Introductionmentioning
confidence: 99%